Mutation breeding: an underutilized strategy for improving finger millet productivity and nutritional quality - Mutanda, Maltase; Figlan, Sandiswa; Shargie, Nemera G.; Gwata, Eastonce T. (Frontiers in Sustainable Food Systems, 2025)
Finger millet is a climate-resilient cereal notable for its exceptional nutritional properties, yet it remains underutilized mainly because of its narrow genetic diversity and slow breeding progress. The loss of genetic variation from prolonged directional selection further hampers the development of improved cultivars suited to changing climatic conditions. Mutation breeding, through the use of physical and chemical mutagens has demonstrated efficacy in generating novel genetic diversity and enhancing desirable traits in finger millet. This review highlights (i) the role of mutation breeding in expanding genetic variability with emphasis on improving grain yield and nutrient composition; (ii) mutagenesis techniques and their application in developing elite mutant lines; and (iii) integration of mutation breeding with advanced omics technologies for efficient screening and target trait selection. Combining mutation breeding with advanced molecular approaches provides a strategic pathway to accelerate the development of high-yielding and nutrient-rich finger millet mutants.